2021
DOI: 10.2196/22564
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Web-Based Sexual Health Literacy Program for Safe Sex Practice for Female Chinese University Students: Multicenter Randomized Controlled Trial

Abstract: Background Sexual health concerns among young adults worldwide help to motivate preventative practices against sexually transmitted infections. To foster better sexual health, sexual health literacy must be enhanced. Little research has been conducted on the impact of gender power dynamics on sexual health, such as sexual coercion, even though the prevalence of sexual coercion remains high in China. Objective This study describes the development and sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…The full-text of 104 studies was screened for eligibility, of which 89 were excluded because they did not include the population of interest (n = 11), was not within the scope of outcome interest (n = 34) or were not the study design of interest (n = 44). Fifteen studies were included in the final analysis [23][24][25][26][35][36][37][38][39][40][41][42][43][44][45][46] (see Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The full-text of 104 studies was screened for eligibility, of which 89 were excluded because they did not include the population of interest (n = 11), was not within the scope of outcome interest (n = 34) or were not the study design of interest (n = 44). Fifteen studies were included in the final analysis [23][24][25][26][35][36][37][38][39][40][41][42][43][44][45][46] (see Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The baseline data of an interactive computer-based intervention (ICBI) project [26] were used to perform the mediated moderation analysis. This project was a randomized controlled trial that estimated the relative effectiveness of an ICBI and the provision of basic information in terms of promoting consistent condom use.…”
Section: Data Collectionmentioning
confidence: 99%
“…At the same time, the fact that young people popularly obtain sex knowledge from the Internet provides a good opportunity for Internet-based intervention programs. A randomized controlled trial reported that an Internet-based sexual health literacy programme for safe sex practice for female Chinese university students could improve knowledge, attitudes, norms, and self-efficacy regarding condom use ( 34 ). Therefore, Internet-based sexual health programmes may be considered to supplement school-based sex education ( 34 ).…”
Section: Discussionmentioning
confidence: 99%